OECD skills strategy implementation guidance for Korea - OECD (OECD publishing, 2021)
A well-coordinated adult learning system is essential to support the achievement of Korea’s long-term goals. The transformational effects of demographic change, digitalisation, globalisation, and most recently COVID-19 on life at work and outside of it amplify the importance of getting adults’ skills right. OECD research shows that individuals, employers and society benefit from adults having higher levels of skills. Korea is a global leader in student performance and tertiary attainment. Yet today, many adults in Korea have skill levels below the OECD average. A significant share of adults face barriers to participate in adult learning. Against the backdrop of a growing awareness about the importance of skills, Korea’s government and stakeholders have a unique opportunity to improve how they share responsibility and work together in the adult learning system. This report outlines how Korea can increase participation in adult learning by strengthening horizontal co-ordination across ministries, vertical co-ordination across levels of government, engagement of stakeholders and financing arrangements. The report provides examples of national and international good practices as well as a series of concrete recommendations to help Korea improve the governance of adult learning and in turn enhance economic growth and social cohesion.
10.1787/f19a4560-en
Keywords: Graue Literatur; Bildungspolitik; Qualifikation; Weiterbildung; Erwachsenenbildung; Südkorea; Education; Employment; Korea; Republic of